A scoping review of maternal health among resettled refugee women in the United States - Sarah Yeo; Yuae Park; Deborah Jean McClelland; John Ehiri; Kacey Ernst; Priscilla Magrath; Halimatou Alaofè (Frontiers Media S.A., 2023)
BackgroundGlobally, refugee women continue to face higher maternity-related risks from preventable complications during pregnancy and childbirth, partly due to high health care costs, unfamiliarity with the healthcare system, language barriers, and discrimination. Nevertheless, there is still a paucity of literature that evaluates the available evidence in the US. This scoping review delineated the body of literature on maternal health among refugee women resettled in the US in order to identify knowledge gaps in the literature and highlight future research priorities and directions for maternal health promotion.MethodsElectronic databases were searched in PubMed, CINAHL, PsycINFO, and EMBASE from inception through July 2021. We included all peer-reviewed study designs; qualitative, quantitative, and mixed method if they reported on refugee women's perinatal health experiences and outcomes in the US.ResultsA total of 2,288 records were identified, with 29 articles meeting the inclusion criteria. Refugee women tend to initiate prenatal care late and have fewer prenatal care visits compared to women born in the US. Some of them were reluctant to get obstetric interventions such as labor induction and cesarean delivery. Despite numerous risk factors, refugee women had generally better maternal health outcomes. Studies have also highlighted the importance of health care providers' cultural competency and sensitivity, as well as the potential role of community health workers as a bridge between refugee women and health care providers.ConclusionsThe scoping review emphasizes the need for early prenatal care initiation and more frequent prenatal care visits among refugee women. Furthermore, more needs to be done to mitigate resistance to obstetric interventions and mistrust. The mechanism by which healthy migrant effects occur could be better understood, allowing protective factors to be maintained throughout the resettlement and acculturation process. The scoping review identifies critical gaps in the literature, such as the underrepresentation of different ethnic groups of refugee women in refugee maternal studies in the US. Since this invisibility may indicate unspoken and unaddressed needs, more attention should be paid to underrepresented and understudied groups of refugee women in order to achieve health equity for all.